Account of Excavations within the Stone Circles of Arran (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article aims, through excavation of standing stone circles on Arran, to interpret what their use might have been when they were constructed. The author provides a description of the excavations, including the dimensions of the stone circles, and highlights any features that might be indicative of their purpose. He also discusses some of the finds that were unearthed during the excavations and includes specialist reports on the human and animal remains that were discovered. Having found both urns and human remains at some of these sites, the author concludes that stone circles on Arran were intended as monuments to mark a burial site.